Differently Abled People and Their Life - S Chhabra (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2016)
Background: Being differently abled is a complex phenomenon and also concept of disability has shifted from individual impairment to social phenomenon. Objective: Present simple review is to get information for planning services and to share. Context Incidence: Numbers vary across countries, lowest reported incidence is from Lithuania (0.58%), highest from Poland (4.0%). European Academy of Childhood Disabilities reported a disabled child rate of 2.5%, additional 8% child population has learning and/or behavioural disorders. In India with lack of awareness, lack of resources, lack of community based services, many babies born with abnormalities continue to live without proper diagnosis, therapy. Sometimes it goes beyond childhood to adulthood, years beyond. Types of disabilities: There are many disabilities which make person differently abled. Hearing loss is one of the most common birth disorders. There are 285 million people with visual impairment worldwide. Limb deformities vary. Psychiatric disorders, by virtue of their very nature, display different patterns of disabilities when compared to physical ailments. Present status: Disability studies are growing as multi-disciplinary field in view of various issues involved. Effects: Having differently abled child in a household affects family's quality of life, parents' gender roles, financial resources, and employment status use of time, health, even occurrence of demographic life events, divorce or birth of another child. Possibilities: Disability must be seen in wider context of human development and social justice. Those working in community disability programmes have responsibility to look into local cultural factors affecting disabled people, communicate findings to policy makers, program managers. There is need for thinking about disabilities as social issue so that needs of disabled persons are met by inclusive rather than exclusive social attitudes, coupled with individually focused rehabilitation process where necessary. Problems are many in resource poor countries. There is need to do community based research.